Слова категорії стану як компонент фразеологічних одиниць - Шелудченко, Світлана Богданівна; Шкаровецька, Алла Дмитрівна; Sheludchenko ., S. B; Shkarovetska, A. D. (Східноєвропейський національний університет імені Лесі Українки, 2014)
Статтю присвячено дослідженню фразеологічних одиниць із компонентом слово категорії стану. Виявлено репертуар слів категорії стану, що конституюють фразеологічні одиниці, укладено інвентар фразеологічних одиниць із досліджуваним компонентом. Розроблено структурну класифікацію фразеологічних одиниць із ком¬понентом слово категорії стану. Встановлено наявність особливого типу фразеологічних одиниць – прислів’їв із компонентом слово категорії стану. This article focuses upon the analysis of the phraseological units containing the word of the category of state as their component. The range of 106 words of the category of state has been determined. The research systematizes 34 words of the category of state constituting phraseological units. The set of 182 phraseological units holding the word of the category of state has been compiled. The article outlines synonymic series the elements of which constitute the phraseological units. Taking into account the words’ of the category of state analysis based on the parameter of structural classification 47 structural models have been singled out. The outlined structural models have been symbolically intergrated into 5 partitions on the basis of quantity. The research demonstrates the specific partition representing the proverbs (as the particular sort of the phraseological units) containing the words of the category of state.
The Words of the Category of State as the Component of Phraseological Units
Keywords: слово категорії стану; word of the category of state; фразеологічна одиниця; phraseological unit; структурна класифікація; structural classification